Advanced Techniques in Wireless Network Design and Security: Heatmap Design, Placement, and Performance Optimization - Vivek Bairy (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Rapid growth in wireless networks with high demands for speedy, reliable, and secure communication necessitates advanced techniques in wireless network design and security. This paper will discuss the advanced techniques in the design and security of wireless networks by studying heatmap-based design and AI-driven optimization. A three-phase approach combines data-informed heatmap evaluation, AI optimization, and security assessment into five different environment types: the urban high-density, office space, industrial region, university precinct, and household. The approaches used included predictive heatmaps built using ConvLSTM, a PSO placement of access points, and the use of reinforcement learning to modulate power signals to maximize received signal strength whilst minimizing interference between access points; security threats had been assessed utilizing AI-aided anomaly detection with Isolation Forest. Results show that there are significant improvements in signal strength, interference reduction, and security detection accuracy than in previous methods. This study contributes towards using AI and heatmap-based techniques for performance optimization of wireless networks with security improvements.